PANCASILA DAN NAHDLATUL ULAMA DALAM BINGKAI NEGARA KESATUAN REPUBLIK INDONESIA (NKRI) - Jamal Ghofir (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2017)
NU's acceptance of Pancasila was deeply and seriously thought NU. This made NU the first community organization to complete its acceptance of Pancasila. However, it has wrongly been used as an excuse to accuse NU for being accommodative in accepting Pancasila; NU acceptance of Pancasila is not based on its accommodative attitude, for it all based in deep thought and consideration. NU decision to leave practical politics and back to become a religious organization is also not an emotional attitude. Not only that NU was the first to receive Pancasila, this organization was also take it without any doubts. While Muhamadiyah came after it. They received Pancasila after the issuance of Law Number 8 Year 1985 on social organization.